Hadis Nabi tentang Kepemimpinan: Prinsip Etis dalam Mencegah Otoritarianisme - Widya Utami (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2025)
This article aims to analyze hadiths related to leadership and the prohibition of authoritarianism in order to identify ethical principles relevant to contemporary Islamic political discourse. Employing a qualitative approach through library research, this study draws on primary sources from canonical hadith collections such as Sahih Muslim and Sunan at-Tirmidhi, complemented by secondary sources from academic literature and Scopus-indexed journals. Data were examined using descriptive-analytical and thematic analysis to extract normative values and contextualize them within modern leadership frameworks. The findings reveal that the Prophetic traditions establish an ethical foundation that rejects authoritarianism and highlight the leader's duty to uphold justice, accountability, and communal welfare. This study contributes to the integration of Prophetic guidance into contemporary leadership discourse, providing an ethical-political framework for addressing authoritarian challenges in modern governance.